In favor of associations: a tribute to Bruno Latour’s (1947-2022) sociology - Almeida, Jalcione (2023)
Bruno Latour is part of a generation of researchers who intended to completely change the way Social Sciences investigate and analyze the production of science and technology. The hesitation before monolithic truths and the reverence for fieldwork constitute key features of Latourian’s heterogeneous work, which are explicit in his studies within scientific laboratories, when the author starts to focus on science and techniques, then hot topics. The Latourian intellectual enterprise, despite (or precisely because of) its heterogeneous and interdisciplinary character, underlines the importance of doubt and hesitation before what is presented as a fact. If such tension is placed in laboratory studies and in the fabrication of scientific truths, Social Sciences do not pass this criticism unscathed: Bruno Latour’s interpretive move shakes the established dominant sociology. As we pay homage to this important author here, our interest is looking over his vast intellectual life. Such a task, however, requires caution. Without intending to expose all of his work, we aim to compile it through movements that we deem relevant to animate new questions for contemporary sociological research.